Pengaruh Berbagai Jenis dan Dosis Kompos terhadap Pertumbuhan Bibit Pisang Barangan pada Tahap Aklimatisasi di Lapangan (Transplanting II) - Eliyanti Eliyanti; Zulkarnain Zulkarnain; Budiyati Ichwan; Sonando Situmorang (Universitas Batanghari, 2023)
This research aimed to investigate the type and dosage of growing media forÂ Barangan banana seedlings during acclimatization in the field (transplanting II). The study was conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Jambi. The trial used a randomized block design with two factors, namely types and doses of compost. The types of compost used were banana pseudostem compost, chicken manure compost, and golden snail compost (kosarmas). While the doses used consisted of 0 mg per kg of planting media, 5 g per kg of planting media, 10 g per kg of planting media, and 15 g per kg of planting media. Each treatment was repeated three times. The results showed that various types and doses of compost did not show significant interactions. Different types and doses of compost media provide good growth of Barangan banana seedlings so that at the age of two months they can be transplanted to the field.The seedlings planted in media with chicken manure compost at a dose of 10 g per kg of planting media tend to showbetter growth performance than other media.Â